Copper-rich phase high-entropy alloy and application thereof in urea synthesis
By introducing functionalized graphene quantum dots and copper-rich phases, the electrocatalytic performance of MnFeCoNiCu2 high-entropy alloy is improved, and the high energy consumption and precious metal scarcity problems of urea electrochemical synthesis in the prior art are solved, and an efficient, environmentally friendly and stable urea synthesis catalyst is achieved.
Patent Information
- Application Number
- CN202411839732.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
AI Technical Summary
When electrochemical synthesis of urea under CO2 and NO3-, the prior art faces problems such as high energy consumption, CO2 emissions and precious metal scarcity, and it is difficult to prepare high-entropy alloy nanoparticles with high electrocatalytic properties and structural homogeneity.
The electrocatalytic performance of urea synthesis of MnFeCoNiCu2 high entropy alloy (MnFeCoNiCu2.0HEA/SHB-GQD) is improved by introducing citric acid, serine and histidine functionalized and boron-doped graphene quantum dots (SHB-GQD) and copper-rich phase. The method includes mixing the metal salt with graphene quantum dots, absorbing and annealing the copper-rich high-entropy alloy nanocatalyst.
A urea synthesis catalyst with green and environmental protection, low cost, excellent electrocatalytic activity and high stability is achieved. The urea synthesis rate reaches 59.01 mmol gcatalyst-1h-1, the Faraday efficiency reaches 26.6%, and the catalyst can be recycled for more than 8 times.
Smart Images

Figure CN119794364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper-rich phase high entropy alloy and application thereof in urea synthesis, belonging to the technical field of electrocatalysis. Background Art
[0002] More than 40% of the world's food production depends on fertilizers. Urea (CO(NH2)2) is an important nitrogen source for fertilizers, with an annual global production of more than 100 million tons. In addition to being used as an agricultural fertilizer, urea is also an important raw material for pharmaceutical and chemical production.
[0003] To date, the main industrial route for producing urea is the Bosch-Meiser process, which uses carbon dioxide (CO2) and ammonia (NH3) under extremely harsh conditions (e.g., 150-200°C, 150-250 bar). This process results in high energy consumption and CO2 emissions, consuming about 80% of the world's NH3 produced by the energy-intensive Haber-Bosch process.
[0004] Nitrate (NO3 - ) is an abundant environmental pollutant, and electrochemical reduction can effectively treat NO3 - Electrochemical nitrate reduction is considered a promising alternative to the Haber-Bosch ammonia synthesis process. Recent studies have shown that electrochemical reduction of CO2 and NO3 under ambient conditions - Can effectively synthesize urea. CO2 and NO3 - Although room temperature electrosynthesis of urea has achieved certain results, it is still a long way from practical application and faces huge challenges. - In the process of urea synthesis, the key step is to generate active *NH2 and *CO intermediates with low energy barriers, which requires the ability to adsorb and activate NO3 - and CO2 to achieve efficient electrocatalysts for CN coupling.
[0005] High entropy alloy (HEA) is a multi-component alloy composed of five or more metallic elements in an equimolar ratio close to . HEA is a stable single-phase solid solution due to the accumulation of entropy. This property allows the elements to be fully mixed to form different multi-element active sites. These active sites can be optimized for specific purposes by selecting the structure and composition of the elements.
[0006] HEAs show outstanding catalytic potential in electrocatalysts such as hydrogen evolution, oxygen evolution, oxygen reduction, CO2 reduction, NH3 decomposition, urea synthesis, energy storage and conversion, etc. Currently, electrocatalysts based on noble metals and precious metals (e.g., Pt, Au, Ru, Rh, etc.) show excellent catalytic performance.
[0007] However, the scarcity and high cost of these precious metals have greatly limited the large-scale and widespread use of such catalysts. In addition, the current methods require the use of special equipment, which is not economically and environmentally feasible, and are difficult to be well applied to the industrial production of HEA nanoparticles. At the same time, since the problem of structural heterogeneity has not been completely solved, it is difficult to synthesize HEA nanoparticles with a single-phase structure. In addition, the HEA nanoparticles have a large particle size and unreasonable elemental composition, resulting in unsatisfactory electrocatalytic performance.
[0008] Therefore, there is an urgent need to develop a high-entropy alloy with mild preparation conditions, high structural homogeneity and good electrocatalytic performance, which has extremely high use value and economic value. Summary of the invention
[0009] In order to solve the above problems, the present invention provides a method for improving the MnFeCoNiCu2 high entropy alloy (MnFeCoNiCu2) by introducing graphene quantum dots (SHB-GQDs) functionalized with citric acid, serine and histidine and doped with boron and a copper-rich phase. 2.0 The method of the invention is green, environmentally friendly, simple and easy to operate, low in cost, and exhibits excellent electrocatalytic activity and high stability.
[0010] The first object of the present invention is to provide a method for preparing a copper-rich phase high entropy alloy, the method comprising:
[0011] (1) dissolving an iron ion salt, a cobalt ion salt, a nickel ion salt, a manganese ion salt and a copper ion salt in water at a molar ratio of 0.5-0.6:0.5-0.6:0.5-0.6:0.5-0.6:0.25-1.2 to obtain a metal salt mixed solution;
[0012] (2) mixing the metal salt mixed solution and the graphene quantum dot solution, absorbing with cotton, and drying to obtain cotton adsorbed with metal salt and graphene quantum dots; wherein the mass ratio of the metal salt, the graphene quantum dots, and the cotton is 0.3-0.8:0.8-1.2:1.0-2.0;
[0013] (3) The cotton adsorbed with metal salts and graphene quantum dots is annealed to prepare a copper-rich high entropy alloy.
[0014] Optionally, the molar ratio of the iron ion salt, the cobalt ion salt, the nickel ion salt, the manganese ion salt and the copper ion salt is 0.5-0.6: 0.5-0.6: 0.5-0.6: 0.5-0.6: 0.8-1.2.
[0015] In one embodiment, the metal salt ions are dissolved in 50-100 mL of water.
[0016] In one embodiment, in step (1), the graphene quantum dots are graphene quantum dots functionalized with citric acid, serine, and histidine and doped with boron, and the preparation method thereof comprises:
[0017] The method is prepared by mixing citric acid, serine, histidine and boric acid in a molar ratio of 0.8-1.2:0.1-0.3:0.8-1.2:0.1-0.5, and heating the mixture at 150-200° C. for reaction for 1-5 hours.
[0018] In one embodiment, in step (1), the iron ion salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate;
[0019] The cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate;
[0020] The nickel ion salt includes one or more of nickel chloride, nickel nitrate, and nickel sulfate;
[0021] The manganese ion salt includes one or more of manganese chloride, manganese nitrate and manganese sulfate;
[0022] The copper ion salt includes one or more of copper chloride, copper nitrate and copper sulfate.
[0023] In one embodiment, in step (3), annealing is performed at 700-900° C. for 1-4 hours;
[0024] Optionally, annealing may be repeated 3 to 5 times.
[0025] The second object of the present invention is to provide a copper-rich phase high entropy alloy prepared by any of the above methods.
[0026] The third object of the present invention is to provide an application of any of the above methods or the above copper-rich phase high entropy alloys in the preparation of urea synthesis catalysts.
[0027] Optionally, the application includes preparing an electrocatalytic working electrode or a solid catalyst.
[0028] A fourth object of the present invention is to provide a urea synthesis catalyst, wherein the urea synthesis catalyst contains the above-mentioned copper-rich phase high entropy alloy.
[0029] The fifth object of the present invention is to provide a method for electrocatalytic synthesis of urea, using the above-mentioned copper-rich phase high entropy alloy to catalyze the reaction in NO3 - and CO2 to catalyze the synthesis of urea.
[0030] In one embodiment, the voltage for catalytic synthesis of urea is -0.4 to -0.6V.
[0031] In one embodiment, the method for preparing an electrocatalytic working electrode comprises the steps of:
[0032] (1) 1 to 5 mg of MnFeCoNiCu 2.0 HEA / SHB-GQDs were dispersed in a mixed solution containing 950 μL of ethanol and 50 μL of 5 wt % Nafion solution;
[0033] (2) The obtained solution was ultrasonically treated for 20 to 30 minutes to obtain MnFeCoNiCu 2.0 HEA / SHB-GQD ink;
[0034] (3) Take 20-30 μL of the ink and drop it on the surface of 1 cm×1 cm carbon paper, and dry it in vacuum at 50-60°C overnight to obtain an electrocatalytic working electrode.
[0035] In one embodiment, the method for electrocatalytic synthesis of urea comprises the steps of:
[0036] (1) Electrocatalytic urea synthesis was performed on a CHI830D workstation equipped with an H-cell system;
[0037] (2) The H-cell system consists of a carbon paper (1 cm × 1 cm) coated with a catalyst as the electrocatalytic working electrode, a standard Ag / AgCl electrode as the reference electrode, and a platinum plate (1 cm × 1 cm) as the counter electrode;
[0038] (3) 0.1-0.5 M KNO3 aqueous solution was used as the electrolyte. Before the reaction, CO2 gas was introduced at room temperature for 30 min. During the reaction, the CO2 flow rate was kept constant at 30 mL min -1 , reaction time 1h.
[0039] (4) Urea was synthesized at a potential of -0.4 V to -0.6 V (vs. RHE).
[0040] Optionally, the voltage in step (4) is -0.5V.
[0041] The sixth object of the present invention is to provide a method for improving the efficiency of urea synthesis, using a copper-rich phase high entropy alloy to catalyze the synthesis of urea; the preparation method of the copper-rich phase high entropy alloy comprises:
[0042] (1) dissolving an iron ion salt, a cobalt ion salt, a nickel ion salt, a manganese ion salt and a copper ion salt in water at a molar ratio of 0.5-0.6:0.5-0.6:0.5-0.6:0.5-0.6:0.25-1.2 to obtain a metal salt mixed solution;
[0043] (2) mixing the metal salt mixed solution and the graphene quantum dot solution, absorbing with cotton, and drying to obtain cotton adsorbed with metal salt and graphene quantum dots; wherein the mass ratio of the metal salt, the graphene quantum dots, and the cotton is 0.3-0.8:0.8-1.2:1.0-2.0;
[0044] (3) The cotton adsorbed with metal salts and graphene quantum dots is annealed to prepare a copper-rich high entropy alloy.
[0045] Optionally, the molar ratio of the iron ion salt, the cobalt ion salt, the nickel ion salt, the manganese ion salt and the copper ion salt is 0.5-0.6: 0.5-0.6: 0.5-0.6: 0.5-0.6: 0.8-1.2.
[0046] In one embodiment, the metal salt ions are dissolved in 50-100 mL of water.
[0047] In one embodiment, in step (1), the graphene quantum dots are graphene quantum dots functionalized with citric acid, serine, and histidine and doped with boron, and the preparation method thereof comprises:
[0048] The method is prepared by mixing citric acid, serine, histidine and boric acid in a molar ratio of 0.8-1.2:0.1-0.3:0.8-1.2:0.1-0.5, and heating the mixture at 150-200° C. for reaction for 1-5 hours.
[0049] In one embodiment, in step (1), the iron ion salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate;
[0050] The cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate;
[0051] The nickel ion salt includes one or more of nickel chloride, nickel nitrate, and nickel sulfate;
[0052] The manganese ion salt includes one or more of manganese chloride, manganese nitrate and manganese sulfate;
[0053] The copper ion salt includes one or more of copper chloride, copper nitrate, and copper sulfate.
[0054] In one embodiment, in step (3), annealing is performed at 700-900° C. for 1-4 hours; optionally, annealing can be repeated 3-5 times.
[0055] Beneficial effects of the present invention
[0056] The present invention improves the MnFeCoNiCu2 high entropy alloy (MnFeCoNiCu) by introducing graphene quantum dots (SHB-GQD) functionalized with citric acid, serine and histidine and doped with boron and a copper-rich phase. 2.0HEA / SHB-GQD) urea synthesis electrocatalytic performance method; the method of the present invention is green, environmentally friendly, simple and easy to operate, low cost, and exhibits excellent electrocatalytic activity and high stability. Specifically:
[0057] (1) The MnFeCoNiCu prepared by the present invention 2.0 The urea synthesis rate of HEA / SHB-GQD reached 59.01mmolg catalyst -1 h -1 ; Faraday efficiency reaches 26.6%;
[0058] (2) The MnFeCoNiCu prepared by the present invention 2.0 HEA / SHB-GQD can be recycled more than 8 times, and the cycle has little effect on the urea synthesis rate and Faradaic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 FTIR spectrum and Raman spectrum of the Cu-rich high entropy alloy nanocatalyst in Example 1; wherein A is MnFeCoNiCu 2.0 FTIR spectrum of HEA / SHB-GQD; B is MnFeCoNiCu 2.0 Raman spectra of HEA / SHB-GQD; C and D are MnFeCoNiCu 2.0 HEA / SHB-GQD、MnFeCoNiCu 1.5 HEA / SHB-GQD and MnFeCoNiCu 1.0 XRD spectrum and magnified (111) diffraction peak pattern of HEA / SHB-GQD;
[0060] Figure 2 MnFeCoNiCu 2.0 Electron microscopy results of HEA / SHB-GQD; A is SEM, B is magnified SEM; C is TEM; D is HRTEM; E is FFT; F is HAADF-STEM image; and G~O are Ni, Cu, Co, Fe, Mn, C, O, B and combined element mapping respectively;
[0061] Figure 3 MnFeCoNiCu 2.0 HEA / SHB-GQD catalytic performance results; wherein A, B and C are the it curve graph, the optimized potential yield graph and the optimized potential Faraday efficiency (FE) graph of the present invention, respectively;
[0062] Figure 4 MnFeCoNiCu 2.0Cyclic performance of HEA / SHB-GQD; wherein A and B are the cyclic stable it curve diagram and the cyclic stable yield and Faraday efficiency (FE) diagram of the present invention, respectively;
[0063] Figure 5 The performance of catalysts prepared with different quantum dots; A is the urea yield graph; B and C are solid UV graphs of catalysts prepared with different quantum dots; D is the polarization curve (LSV) graph of catalysts prepared with different quantum dots
[0064] Figure 6 The catalytic performance diagram of urea synthesis using high entropy alloy (MnFeCoNiCuxHEA, x=1.0, 1.5, 2.0) nanocatalysts with different atomic ratios;
[0065] Figure 7 This is a diagram showing the catalytic performance of synthesizing urea using nanocatalysts of high entropy alloys with different element combinations according to the present invention. DETAILED DESCRIPTION
[0066] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0067] Test method:
[0068] The preparation method of the electrocatalytic working electrode comprises the following steps:
[0069] (1) 2 mg of MnFeCoNiCu2.0 HEA / SHB-GQDs were dispersed in a mixed solution containing 950 μL of ethanol and 50 μL of 5 wt.% Nafion solution;
[0070] (2) The obtained solution was ultrasonically treated for 30 min to obtain MnFeCoNiCu 2.0 HEA / SHB-GQD ink;
[0071] (3) Take 20 μL of ink and drop it on the surface of 1 cm × 1 cm carbon paper and dry it in vacuum at 60°C overnight to obtain a working electrode.
[0072] The electrocatalytic synthesis method of urea comprises the following steps:
[0073] (1) Electrocatalytic urea synthesis was performed on a CHI830D workstation equipped with an H-cell system. The H-cell system consists of a carbon paper (1 cm × 1 cm) coated with a catalyst as the working electrode, a standard Ag / AgCl electrode as the reference electrode, and a platinum plate (1 cm × 1 cm) as the counter electrode.
[0074] (2) 0.1 M KNO3 aqueous solution was used as the electrolyte. Before the reaction, CO2 gas was introduced at room temperature for 30 min. During the reaction, the CO2 flow rate was kept constant at 30 mL min -1 , reaction time 1h, urea was prepared.
[0075] The urea concentration was determined by the diacetyl monoxime method, and the steps are as follows:
[0076] (1) A series of standard urea solutions (0, 0.5, 1, 2, 5 and 10 ppm) were prepared;
[0077] 10 mL of concentrated phosphoric acid and 30 mL of concentrated sulfuric acid were added to 60 mL of distilled water and mixed, and then 10 mg of FeCl3 was added to obtain solution A;
[0078] (2) 250 mg of diacetyl monoxime (DAMO) and 5 mg of thiourea (TSC) were dissolved in 50 mL of distilled water to obtain solution B;
[0079] (3) 2 mL of solution A and 1 mL of solution B are added to 1 mL of electrolyte (or 1 mL of standard urea solution) taken from the cathode chamber and mixed evenly;
[0080] (4) The mixed solution was heated to 90°C in a water bath, kept warm for 40 min, cooled to 25°C, and the absorbance was measured at 525 nm to calculate the urea concentration.
[0081] The raw materials used in the examples are:
[0082] Iron (III) chloride hexahydrate (FeCl3.6H2O, ≥99.0%; hereinafter referred to as iron chloride), nickel chloride hexahydrate (NiCl2·6H2O, ≥98.0%; hereinafter referred to as nickel chloride), cobalt chloride hexahydrate (CoCl2·6H2O, ≥99.0%; hereinafter referred to as cobalt chloride), manganese (II) chloride tetrahydrate (MnCl2·4H2O, 98.0%; hereinafter referred to as manganese chloride), copper (II) sulfate pentahydrate (CuCl2·2H2O, ≥99.0%; hereinafter referred to as copper chloride), citric acid monohydrate (C6H8O7·H2O, AR; hereinafter referred to as citric acid), histidine (C6H9N3O2, AR), l-serine (C3H7NO3, AR; hereinafter referred to as serine), boric acid (H3BO3, AR), potassium nitrate (KNO3, AR), urea (CH4N2O, AR), diacetyl imide (C4H7NO2, AR), thiourea (TSC, AR), potassium sulfate (K2SO4, AR), and anhydrous ethanol (C2H60, AR) were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0083] Example 1: Preparation of Cu-rich high entropy alloy nanocatalyst (MnFeCoNiCu2.0 HEA / SHB-GQD)
[0084] 1. Preparation of SHB-GQDs
[0085] (1) citric acid, serine, histidine and boric acid were dispersed in an appropriate amount of deionized water at a molar ratio of 1:0.2:1:0.3 and ultrasonicated for 30 min to obtain a transparent mixed solution;
[0086] (2) The mixture was placed in a forced air drying oven at 180° C. for 3 h to obtain N and B doped functionalized graphene quantum dots (solid), which were named SHB-GQD.
[0087] 2. Preparation of Cu-rich high entropy alloy nanocatalyst, the steps are as follows:
[0088] (1) dissolving ferric chloride (0.5728 mmol), cobalt chloride (0.5728 mmol), nickel chloride (0.5728 mmol), manganese chloride (0.5728 mmol) and cupric chloride (1.1456 mmol) in 50 mL of ultrapure water to obtain a metal salt mixed solution;
[0089] (2) The metal salt mixed solution was dropped into an aqueous solution containing 0.9864 g of SHB-GQD and stirred (500 rpm) for 3 h. The volume ratio of the metal salt mixed solution to the SHB-GQD aqueous solution was 1:4. 1.644 g of cotton was used to absorb it completely and vacuum dried at 60 ° C for 24 h to obtain cotton adsorbing metal salts and carbon quantum dots.
[0090] (3) Cotton adsorbed with metal salts and carbon quantum dots was annealed at 900 °C for 4 h in argon containing 5% H2, with a heating rate of 5 °C min -1 , and obtained a Cu-rich high-entropy alloy nanocatalyst, named MnFeCoNiCu2HEA / SHB-GQD.
[0091] 3. Changing the Cu content in Cu-rich high entropy alloy nanocatalysts
[0092] Based on step 1, the amount of copper chloride was changed to 0.5728 mmol and 0.8592 mmol respectively to prepare Cu-rich high entropy alloy nanocatalysts with different Cu contents, which were named MnFeCoNiCu 1.0 HEA / SHB-GQD、MnFeCoNiCu 1.5 HEA / SHB-GQD.
[0093] 4. Characterization of Cu-rich high entropy alloy nanocatalysts
[0094] Take the MnFeCoNiCu prepared in steps 2 and 3 2.0HEA / SHB-GQD、MnFeCoNiCu 1.0 HEA / SHB-GQD and MnFeCoNiCu 1.5 HEA / SHB-GQD, structural characterization, the results are as follows:
[0095] (2) FTIR spectroscopy and Raman spectroscopy
[0096] MnFeCoNiCu 2.0 FTIR and Raman spectra of HEA / SHB-GQDs are shown in Figure 2 Figure 1 As shown in A and B. The results show that MnFeCoNiCu 2.0 HEA / SHB-GQD at 3421, 2854, 1632, 1454, 1100 and 725 cm -1 There are 7 main infrared absorption peaks and absorption bands.
[0097] Among them, the wave number is between 4000 and 3300 cm -1 The infrared absorption band between 2854cm and 2864cm is caused by the stretching vibration of OH, NH and unsaturated -CH bonds. -1 The infrared absorption peak at the wave number is caused by the stretching vibration of saturated hydrocarbons; the wave number is about 1632cm -1 The infrared absorption band is caused by the stretching vibration of C=O and C=C bonds; 1354cm -1 The infrared absorption peak at the wave number is caused by the stretching vibration of the -O bond; -1 The infrared absorption peak at wave number 615cm is caused by the stretching vibration of the C-O-C bond; -1 The infrared absorption peak at wave number is caused by the out-of-plane bending vibration of -CH3 group; FTIR analysis results show that MnFeCoNiCu 2.0 HEA / SHB-GQDs contain -OH, -COOH, -NH-, and -CH3.
[0098] MnFeCoNiCu 2.0 Raman spectrum of HEA / SHB-GQD at 1335 cm -1 and 1617cm -1 There are two Raman absorption peaks at the center, corresponding to the D peak and G peak of graphene. The intensity ratio of the D peak to the G peak (I D / I G ) is 1.339. The higher I D / I G It shows that graphene sheets on MnFeCoNiCu 2.0 HEA / SHB-GQDs have good dispersion.
[0099] MnFeCoNiCu 2.0 HEA / SHB-GQD、MnFeCoNiCu 1.5 HEA / SHB-GQD and MnFeCoNiCu 1.0 The XRD patterns of HEA / SHB-GQD and the magnified (111) diffraction peak are shown in Figure 2. Figure 1 As shown in C and D.
[0100] The results show that there is a broad diffraction peak at about 25° between 10° and 40° ( Figure 1 C), the peak can be assigned to the (002) crystal plane of graphene. Due to the poor crystallinity of graphene, its diffraction peak is weak and broad.
[0101] MnFeCoNiCu 2.0 HEA / SHB-GQD、MnFeCoNiCu 1.5 HEA / SHB-GQD and MnFeCoNiCu 1.0 There are eight diffraction peaks at 43.4°, 43.8°, 50.5°, 51.0°, 74.2°, 75.1°, 90.2° and 91.3° in the XRD spectrum of HEA / SHB-GQD; among them, the four peaks at 43.4°, 50.5°, 74.2° and 90.2° belong to (111), (200), (220), (311) and (222) of the FCC1 phase, respectively; the four peaks at 43.8°, 51.0°, 75.1° and 91.3° belong to (111), (200), (220), (311) and (222) of the FCC2 phase, respectively.
[0102] The above results show that the Cu-rich high entropy alloy nanocatalyst MnFeCoNiCu prepared in Example 1 2.0 HEA has a dual FCC phase structure.
[0103] In the FCC1 and FCC2 phases, Figure S4 shows that the FCC1 phase is a copper-rich phase. As the Cu ratio increases, the diffraction intensity of the FCC1 phase increases rapidly ( Figure 1 D) Cu 2+ It is the most easily reducible metal in HEA, and its reduction potential is relatively low. The rapid accumulation of copper atoms will lead to the formation of copper-rich phase, especially when the copper content is high.
[0104] (2) Electron microscopy results
[0105] Figure 2 MnFeCoNiCu 2.0SEM, TEM, HRTEM and HAADF-STEM of HEA / SHB-GQDs, as well as elemental mapping of Ni, Cu, Co, Fe, Mn, C, O, B and combined elements. SEM images show the presence of a three-dimensional carbon network structure ( Figure 2 A), which is due to the carbonization of cotton during thermal annealing. The presence of carbon network can accelerate the electron / electrolyte transfer during electrocatalytic urea synthesis.
[0106] The magnified SEM image shows that there are many white spheres on the surface of the carbon fiber ( Figure 2 B), indicating the presence of MnFeCoNiCu 2.0 HEA nanoparticles. SEM and TEM analysis results confirmed that MnFeCoNiCu 2.0 HEA nanoparticles are spherical with an average particle size of 114±1.2nm ( Figure 2 B); In addition, TEM images show that the spheres are irregular in shape ( Figure 2 C). This may be related to the formation of a copper-rich phase. There is a 0.194 nm spacing on the HRTEM image, corresponding to the MnFeCoNiCu 2.0 The (200) crystal plane of HEA ( Figure 2 D). Figure 2 The rectangular and square areas in D are transformed by FFT. From Figure E, it can be observed that the lattice fringes of SHB-GQD are 0.345nm, corresponding to the carbon (002) crystal plane, and the lattice fringes of cotton are 0.381nm, corresponding to the carbon (002) crystal plane. HAADF-STEM and elemental mapping show that Mn, Fe, Co, Ni, Cu, C, O and B elements are in MnFeCoNiCu 2.0 Spatial distribution of HEA nanoparticles ( Figure 2 F~ Figure 2 O). Mn, Fe, Co, Ni and Cu elements come only from MnFeCoNiCu 2.0 HEA nanoparticles, carbon (C) and boron (B) only come from SHB-GQDs.
[0107] The elemental analysis results also confirmed that MnFeCoNiCu 2.0 HEA / SHB-GQD is composed of MnFeCoNiCu 2.0 HEA nanoparticles and SHB-GQDs. Elemental mapping of Mn, Fe, Co, Ni, and Cu and MnFeCoNiCu 2.0 The shapes of HEA nanoparticles are consistent, i.e., MnFeCoNiCu 2.0 HEA / SHB-GQD has good chemical uniformity. The MnFeCoNiCu 2.0The contents of Mn, Fe, Co, Ni and Cu in HEA / SHB-GQDs. The molar ratio of Mn, Fe, Co, Ni and Cu is 1:1:1:1:2, which is consistent with the 2.0 The composition of HEA is consistent. According to the total mass of each metal element, MnFeCoNiCu 2.0 Mass ratio of HEA, MnFeCoNiCu 2.0 HEA in MnFeCoNiCu 2.0 The mass ratio in HEA / SHB-GQD is 23.81 wt.%.
[0108] Example 2: Cu-rich high entropy alloy nanocatalyst (MnFeCoNiCu 2.0 HEA / SHB-GQD) optimized potential test
[0109] Take the MnFeCoNiCu prepared in Example 1 2.0 HEA / SHB-GQD was used for electrocatalytic urea synthesis on a CHI830D workstation equipped with a 3-electrode H-cell system.
[0110] A 0.1 M KNO3 aqueous solution was used as the electrolyte. Before the reaction, CO2 gas was introduced at room temperature for 30 min. During the reaction, the CO2 flow rate was kept constant at 30 mL min. -1 , reaction time 1h. Urea was synthesized at -0.3V, -0.4V, -0.5V, -0.6V, -0.7V (vs. RHE) potentials, and the potential with the highest urea yield was screened out, that is, the optimized potential test was performed. The results are as follows Figure 3 shown.
[0111] Figure 3 A, B and C are MnFeCoNiCu 2.0 IT curves, urea yield, and Faradaic efficiency of HEA / SHB-GQD electrode at -0.3, -0.4, -0.5, -0.6, and -0.7 V versus RHE in CO2-saturated 0.1 M KNO3 electrolyte for 60 min.
[0112] The results show that the current density is less than zero at all potentials, indicating that CO2 and NO3 - can be reduced, and as the potential increases, CO2 and NO3 - The reduction rate is accelerated, resulting in an increase in current density ( Figure 3 A).
[0113] However, the changes in urea yield and Faradaic efficiency do not follow this pattern. The urea yield increases rapidly when the potential is below -0.5 V ( Figure 3 B), reaching a maximum value (59.01mmol g) at a potential of -0.5V. catalyst -1 h -1 ), with the highest Faraday efficiency (26.6%) ( Figure 3 C) and then decreased.
[0114] Therefore, in order to obtain a higher urea yield and avoid serious side effects, -0.5 V potential was selected as the MnFeCoNiCu 2.0 Working potential of electrocatalytic synthesis of urea under HEA / SHB-GQD catalysis.
[0115] Example 3: Cu-rich high entropy alloy nanocatalyst (MnFeCoNiCu 2.0 HEA / SHB-GQD) Cyclic Stability Test
[0116] Take the MnFeCoNiCu prepared in Example 1 2.0 The electrocatalytic stability of HEA / SHB-GQD was tested on a CHI830D workstation equipped with a 3-electrode H-cell system.
[0117] 0.1M KNO3 aqueous solution was used as the electrolyte. Before the reaction, CO2 gas was introduced at room temperature for 30 min. During the reaction, the CO2 flow rate was kept constant at 30 mL min. -1 Each reaction time is 1h, and the cycle test is performed 8 times at a potential of -0.5V (vs.RHE), i.e., the cycle stability test. Figure 4 shown.
[0118] Figure 4 A and B are MnFeCoNiCu 2.0 The HEA / SHB-GQD electrode was tested for 8 cycles at -0.5 V in a CO2-saturated 0.1 M KNO3 electrolyte, and the 60 min IT curves, urea yields, and Faradaic efficiencies (FEs) were obtained. Figure 4 It can be seen that in the 8-cycle test, the shapes and current densities of all it curves are very similar. This indicates that the reduction of electroactive components and side reactions caused by electrode material stripping are almost negligible. After 8 cycles, the urea yield remained at 56.74 mmol g catalyst -1 , FE is 26.33%. The results show that 8 cycles only reduce the urea yield by 3.85% and the FE value by 1.02%.
[0119] Comparative Example 1: Preparation of high entropy alloy (MnFeCoNiCu) with different quantum dots 2.0 HEA) nanocatalyst
[0120] On the basis of Example 1, the types of quantum dots were changed respectively: quantum dots prepared from citric acid (GQD), quantum dots prepared from citric acid and histidine (H-GQD), quantum dots prepared from citric acid, histidine and serine (SH-GQD), quantum dots prepared from citric acid, histidine, serine and boric acid (SHB-GQD), and the remaining steps were consistent with Example 1 to prepare nanocatalysts composited with different quantum dots and high entropy alloys. The electrocatalytic performance of the synthesized urea was tested by solid ultraviolet and electrochemical methods, and the results were as follows: Figure 5 shown.
[0121] Figure 5 A shows the MnFeCoNiCu in CO2-saturated 0.1M KNO3 electrolyte at -0.5V. 2.0 HEA / SHB-GQD、MnFeCoNiCu 2.0 HEA / SH-GQD、MnFeCoNiCu 2.0 HEA / H-GQD and MnFeCoNiCu 2.0 Urea yield at 60 min under HEA / GQD.
[0122] The results show that MnFeCoNiCu 2.0 The urea yield of HEA / SHB-GQD electrode reached 59.01 mmol g catalyst -1 h -1 , has good catalytic activity, and this value is significantly higher than that of MnFeCoNiCu 2.0 HEA / SH-GQD (40.52 mmol g catalyst - 1 h -1 )、MnFeCoNiCu 2.0 HEA / H-GQD(33.28mmol g catalyst -1 h -1 ) and MnFeCoNiCu 2.0 HEA / GQD(18.09mmol g catalyst -1 h -1 ), which increased by 45.6%, 77.3%, and 226%, respectively. The above results provide new ideas for the rational design of GQDs to improve electrocatalytic activity.
[0123] Figure 5B shows that different GQDs exhibit different UV-visible diffuse reflectance behaviors. GQD exhibits a strong absorption capacity for UV light and a weak absorption capacity for visible light, especially for visible light with a wavelength greater than 620nm; the introduction of histidine (H-GQD) significantly enhances its absorption capacity for UV and visible light, but H-GQD still has a weak absorption capacity for visible light with a wavelength greater than 620nm.
[0124] By introducing serine, the performance was significantly improved, and SH-GQD had a strong light absorption capacity for visible light with a wavelength greater than 620nm, and the introduction of boron atoms further strengthened this ability. It can be seen that SHB-GQD has the best absorption capacity for visible light with a wavelength greater than 620nm.
[0125] The relationship between the transformed Kubelka-Munk function and the light energy of GQD, H-GQD, SH-GQD and SHB-GQD is shown in the figure below: Figure 5 C. By extending the tangent of the curve to intersect the horizontal axis, the band gap energy (Eg) of the semiconductor material can be determined. The results show that the Eg value of GQD is large, 2.43eV, and the conductivity is low; the Eg value of H-GQD drops to 2.36eV, the Eg value of SH-GQD drops to 2.22eV, and the Eg value of SHB-GQD drops to 2.06eV. This indicates that the introduction of histidine, serine, and boron leads to a decrease in Eg value.
[0126] Since GQD is a semiconductor, MnFeCoNiCu 2.0 HEA is a conductor, GQD and MnFeCoNiCu 2.0 The incorporation of HEA induces the generation of Schottky heterojunction at the interface. This promotes electron transfer at the interface, thereby improving the electrocatalytic activity. The GQD with a smaller Eg value has a faster electron transfer process at the interface and exhibits better catalytic activity. The results show that MnFeCoNiCu 2.0 HEA / SHB-GQDs have the best catalytic activity for urea synthesis.
[0127] Therefore, the MnFeCoNiCu 2.0 HEA / SHB-GQD、MnFeCoNiCu 2.0 HEA / SH-GQD、MnFeCoNiCu 2.0 HEA / H-GQD and MnFeCoNiCu 2.0 The LSV curve of HEA / H-GQD electrode at -1.3~0.1V potential in CO2 saturated 0.1M KNO3 electrolyte is shown in the following figure. Figure 5 As shown in D.
[0128] For MnFeCoNiCu 2.0 For HEA / GQD, the LSV current density is close to zero when the potential is lower than -0.57 V, indicating that urea synthesis cannot be carried out at a potential lower than -0.57 V. However, with the increase of the reduction potential, the LSV current density increases rapidly, showing a fast urea synthesis process.
[0129] The minimum potential required for the synthesis of urea is named the onset potential (Es), and the relatively high Es value confirms that MnFeCoNiCu 2.0 HEA / GQDs only have low electrocatalytic activity for urea synthesis. 2.0 HEA / H-GQD replaces MnFeCoNiCu 2.0 When HEA / GQD is used, the Es value drops to -0.43 V, which verifies the MnFeCoNiCu 2.0 HEA / H-GQD ratio of MnFeCoNiCu 2.0 HEA / GQD has better electrocatalytic activity. 2.0 HEA / SH-GQD replaces MnFeCoNiCu 2.0 When HEA / H-GQD was used, the Es value was further reduced to -0.0041 V, and the electrocatalytic activity was significantly enhanced. 2.0 HEA / SHB-GQD has the best electrocatalytic activity (Es is 0.1 V).
[0130] Comparative Example 2: Preparation of high entropy alloys (MnFeCoNiCu) with different atomic ratios x HEA / SHB-GQD, x=1.0,1.5,2.0) nanocatalyst
[0131] Take the MnFeCoNiCu prepared in Example 1 2.0 HEA / SHB-GQD、MnFeCoNiCu 1.5 HEA / SHB-GQD and MnFeCoNiCu 1.0 HEA / SHB-GQD was used to test its electrocatalytic performance in synthesizing urea. Figure 6 shown.
[0132] Depend on Figure 6 It can be seen that the electrocatalytic activity of catalysts with different copper contents is significantly different. The urea yields are: MnFeCoNiCu 1.0 HEA / SHB-GQD 28.16mmol g catalyst -1 h -1 、MnFeCoNiCu 1.5HEA / SHB-GQD37.81mmol g catalyst -1 h -1 and MnFeCoNiCu 2.0 HEA / SHB-GQD 59.01mmol g catalyst -1 h -1 The results show that MnFeCoNiCu 2.0 HEA / SHB-GQD has the best catalytic activity for urea synthesis among the three electrocatalysts.
[0133] Comparative Example 3: Preparation of different element combinations (Mn, MnFe, MnFeCo, MnFeCoNi, MnFeCoNiCu 2.0 HEA) nanocatalyst
[0134] On the basis of Example 1, the combination of elements in the high entropy alloy was changed respectively, and the SHB-GQD was coordinated and chelated according to the combination of Mn, MnFe, MnFeCo, MnFeCoNi, and MnFeCoNiCu (the molar ratio of metal ions was 1:1), and the remaining steps were consistent with Example 1 to prepare different nanocatalysts. The electrocatalytic performance of the synthesized urea was tested by electrochemical method, and the results were as follows: Figure 7 shown.
[0135] Figure 7 For Mn / SHB-GQD, MnFe / SHB-GQD, MnFeCo / SHB-GQD, MnFeCoNi / SHB-GQD and MnFeCoNiCu 2.0 The yield of electrocatalytic urea synthesis over HEA / SHB-GQD electrode in CO2-saturated 0.1 M KNO3 electrolyte at -0.5 V for 60 min.
[0136] The urea yields of Mn / SHB-GQD were 4.47 mmol g catalyst -1 h -1 、15.32mmolg of MnFe / SHB-GQD catalyst -1 h -1 , 20.84mmol g of MnFeCo / SHB-GQD catalyst -1 h -1 、MnFeCoNi / SHB-GQD 32.58mmolg catalyst -1 h -1 and MnFeCoNiCu 2.0HEA / SHB-GQD: 59.01 mmol g catalyst -1 h -1 The results showed that the introduction of each metal element improved the urea yield and showed enhanced electrocatalytic activity. Among the five electrocatalysts used, MnFeCoNiCu 2.0 HEA / SHB-GQD has the best electrocatalytic activity. The high entropy effect generated by the mixture of Mn, Fe, Co, Ni and Cu is the main reason for the excellent catalytic activity of the catalyst.
[0137] Comparative Example 4: Comparison of catalytic performance of urea synthesis using different catalysts
[0138] The MnFeCoNiCu prepared in Example 1 2.0 The catalytic performance of HEA / SHB-GQD in synthesizing urea is compared with that of currently reported catalysts, and the results are shown in Table 1.
[0139] Table 1 Comparison results of catalytic performance
[0140]
[0141] In summary, the results show that the MnFeCoNiCu prepared by the present invention 2.0 HEA / SHB-GQD has both high urea yield and Faradaic efficiency, which is superior to the existing technology.
[0142] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a copper-rich phase high entropy alloy, characterized in that: The method comprises: (1) dissolving an iron ion salt, a cobalt ion salt, a nickel ion salt, a manganese ion salt and a copper ion salt in water at a molar ratio of 0.5-0.6:0.5-0.6:0.5-0.6:0.5-0.6:0.25-1.2 to obtain a metal salt mixed solution; (2) mixing the metal salt mixed solution and the graphene quantum dot solution, absorbing with cotton, and drying to obtain cotton adsorbed with metal salt and graphene quantum dots; wherein the mass ratio of the metal salt, the graphene quantum dots, and the cotton is 0.3-0.8:0.8-1.2:1.0-2.0; (3) The cotton adsorbed with metal salts and graphene quantum dots is annealed to prepare a copper-rich high entropy alloy.
2. The method according to claim 1, characterized in that In step (1), the graphene quantum dots are graphene quantum dots functionalized with citric acid, serine, and histidine and doped with boron, and the preparation method thereof comprises: The method is prepared by mixing citric acid, serine, histidine and boric acid in a molar ratio of 0.8-1.2:0.1-0.3:0.8-1.2:0.1-0.5, and heating the mixture at 150-200° C. for reaction for 1-5 hours.
3. The method according to claim 1, characterized in that In step (1), the iron ion salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate; The cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate; The nickel ion salt includes one or more of nickel chloride, nickel nitrate, and nickel sulfate; The manganese ion salt includes one or more of manganese chloride, manganese nitrate and manganese sulfate; The copper ion salt includes one or more of copper chloride, copper nitrate and copper sulfate.
4. The method according to claim 1, characterized in that: In step (3), annealing is performed at 700-900° C. for 1-4 hours.
5. A copper-rich phase high entropy alloy prepared by the method according to any one of claims 1 to 4.
6. Use of the method according to any one of claims 1 to 4 or the copper-rich phase high entropy alloy according to claim 5 in the preparation of a urea synthesis catalyst; Optionally, the application includes preparing an electrocatalytic working electrode or a solid catalyst.
7. A urea synthesis catalyst, characterized in that The urea synthesis catalyst contains the copper-rich phase high entropy alloy according to claim 5.
8. A method for electrocatalytic synthesis of urea, characterized in that: Using the copper-rich phase high entropy alloy of claim 5, in NO3 - and CO2 to catalyze the synthesis of urea.
9. The method according to claim 8, characterized in that The voltage for catalytic synthesis of urea is -0.4 to -0.6V.
10. A method for improving urea synthesis efficiency, characterized in that: A copper-rich phase high entropy alloy is used to catalyze the synthesis of urea; the preparation method of the copper-rich phase high entropy alloy comprises: (1) dissolving an iron ion salt, a cobalt ion salt, a nickel ion salt, a manganese ion salt and a copper ion salt in water at a molar ratio of 0.5-0.6:0.5-0.6:0.5-0.6:0.5-0.6:0.25-1.2 to obtain a metal salt mixed solution; (2) mixing the metal salt mixed solution and the graphene quantum dot solution, absorbing with cotton, and drying to obtain cotton adsorbed with metal salt and graphene quantum dots; wherein the mass ratio of the metal salt, the graphene quantum dots, and the cotton is 0.3-0.8:0.8-1.2:1.0-2.0; (3) The cotton adsorbed with metal salts and graphene quantum dots is annealed to prepare a copper-rich high entropy alloy.
Citation Information
Cited By
Industrial electrode for electrocatalytic synthesis of urea as well as preparation and application of industrial electrode
CN120425405A